A study of efficacy of intramuscular injection tramadol as labour analgesic and labour accelerator in 400 primigravida patients in latent phase of first stage of labour - Vanitha, M.; Muthulakshmi, N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Labour pain is among the most severe pain experienced by women. Most women like to experience labour birth with active involvement and as naturally as possible. Hence, the need for analgesia to overcome labour pains is highly requested by women today. In developing nations where availability of facilities is the main limiting factor, intra muscular opioids can be used. The aim was to know the effect of Tramadol in labour analgesia and reduction in the duration of labour and to know the maternal and neonatal outcome after administration of Tramadol Methods: This study was conducted in tertiary teaching care hospital in 400 low risk primigravidae who fulfilled selection criteria with full-term pregnancy with vertex presentation in late latent phase of labour were selected and given 100 mg tramadol hydrochloride intramuscularly. Results: The degree of pain relief in 1 st and 2 nd stage of labour, duration of labour, Apgar score of neonates and side effect of drugs were studied. In this study 23.5% of patients had grade II pain, 38.5% of patients had grade III pain and 38% of patients had no pain relief after Tramadol administration. Before drug, the mean pain score is 3.86 in stage I. After drug administration the mean pain score is 3.14 in stage I and 3.81 in stage II. The duration of first and second stage of labour also shortened. Conclusions: In low risk Primigravidae, IM Tramadol hydrochloride appears to be effective without side effects. Hence, in developing nations, where availability of facilities is the main limiting factor, IM opioids can be considered as suitable alternatives.